2017
DOI: 10.1002/jgm.2939
|View full text |Cite
|
Sign up to set email alerts
|

Integration of expression quantitative trait loci and pleiotropy identifies a novel psoriasis susceptibility gene, PTPN1

Abstract: The results of the present study highlight the expression quantitative trait loci enrichment and pleiotropy in psoriasis and schizophrenia, and also suggest a possible key role of the PTPN1 gene in the etiology of psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…Besides these, Yin et al evaluated the common genetic factors shared between psoriasis and schizophrenia. Even though they reported that any common variant was not found between two diseases, they claimed that PTPN1 gene may be a novel-susceptible gene for psoriasis which interacts with well-known susceptible genes for psoriasis such as NFKBA, STAT3, and TYK2 genes [ 7 ]. Similarly, we showed significantly upregulated PTPN1 gene expression in the lesional psoriatic skin than the non-lesional skin of the same patients, and also healthy skin of controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these, Yin et al evaluated the common genetic factors shared between psoriasis and schizophrenia. Even though they reported that any common variant was not found between two diseases, they claimed that PTPN1 gene may be a novel-susceptible gene for psoriasis which interacts with well-known susceptible genes for psoriasis such as NFKBA, STAT3, and TYK2 genes [ 7 ]. Similarly, we showed significantly upregulated PTPN1 gene expression in the lesional psoriatic skin than the non-lesional skin of the same patients, and also healthy skin of controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the expression of EREG, PTPN1, and SER-PINB7 genes have been evaluated in a few studies, and these genes are claimed to be novel susceptible genes for psoriasis especially related to keratinocytes, adipocytes, other immunological cells [2,[7][8][9][10]. Unlike these studies, we investigated all these genes together, at the tissue level, and in more samples.…”
Section: Objectivesmentioning
confidence: 99%
“…Calculation of cFDR , ccFDR and GPA. Both cFDR and GPA are well-established pleiotropic methods for incorporating GWAS data at the summary statistic level, which have been widely applied to many diseases or traits [45][46][47][48] . We briefly summarized both approaches in the following section.…”
Section: Data Processingmentioning
confidence: 99%
“…This may assist in explaining the epidemiological association that exists between PsO and SCZ. Yin et al (2017) conducted PsO and SCZ whole blood expression quantitative trait loci (eQTL) analysis and observed a significant pleiotropic effect between PsO and SCZ. GWAS data analysis of PsO and SCZ shows the abundance of eQTL in whole blood, and reveals that the common variants of these two diseases are more likely to confer eQTL effects.…”
Section: Metabolic Syndromementioning
confidence: 99%